Asthma and Asthma Medication Are Common among Recreational Athletes Participating in Endurance Sport Competitions - Amanda Näsman; Tommie Irewall; Ulf Hållmarker; Anne Lindberg; Nikolai Stenfors (Canadian Respiratory Journal)
Background. Asthma prevalence is high among elite endurance athletes, but little is known about its prevalence among competitive recreational athletes. The aim of this study was to determine the prevalence of self-reported asthma and asthma medication use among competitive recreational endurance athletes and their association with training. Methods. A web survey on asthma and medication was conducted among 38,603 adult participants of three Swedish endurance competitions (cross-country running, cross-country skiing, and swimming). Results. The overall response rate was 29%. The prevalence of self-reported asthma (physician-diagnosed asthma and use of asthma medication in the last 12 months) was 12%. Among those reporting asthma, 23% used inhaled corticosteroids and long-acting beta-agonists daily. We found no association between training volume and daily use of asthma medication, except a trend in relation to short-acting beta-agonists. Independent predictors of self-reported asthma were female sex, allergic rhinitis, previous eczema, family history of asthma, cycling, and training for >5 h 50 min/week. Conclusions. The prevalence of self-reported asthma among Swedish competitive recreational endurance athletes appears to be higher than that in the general Swedish population. A large proportion of recreational athletes were reported with asthma use medications, indicating an association between high physical activity and self-reported asthma among competitive recreational athletes.